CASE REPORT OF A RARE JAW TUMOUR ; ITS BASIC LINE OF DIAGNOSIS - DR. KOUSHIK DEWAN; DR. TANUSHREE MONDAL (International Journal of Pharma and Bio Sciences, 2015)
Sarcoma itself is a rare entity in intraoral region and osteosarcoma is not an exception from this data. Here we are presenting a case of osteosarcoma in a 31 year old newly married young male which was simply presented as toothache and so that primarily misdiagnosed as dental infection. With a battery of investigations like Orthopentogram, FNA, Histopathological Examination, CT scan etc, ultimately we reached our diagnosis & an oncological plan was made to treat him with multiple neo-adjuvant chemotherapy followed by radical surgical resection along with a margin of normal surrounding tissue, and chemotherapy.